2019
DOI: 10.1088/1361-6641/ab23ab
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a GaAs/GaAsBipinsolar cell

Abstract: The structural and photovoltaic properties of the GaAs/GaAsBi pin solar cell with GaAs 0.983 Bi 0.017 active layer are investigated by optical and electrical measurement techniques. The bandgap of GaAsBi active layer is determined to be 1.3 eV at room temperature. Current density-voltage (J-V) under AM 1.5G spectrum and spectral response measurements are carried out to determine photovoltaic properties of the solar cell. The presence of a midgap trap levels in GaAsBi active layer is identified by deep level tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…At high bias, the current is lower than predicted, which would normally be ascribed to parasitic series resistance, but in this case the data cannot be fit by assuming series resistance at high bias. A similar effect has been seen in other reports on GaAsBi diodes [15,16]. This report will focus on the regime in which the diode behaviours can be well-fitted using the Shockley diode equation.…”
Section: Resultssupporting
confidence: 76%
“…At high bias, the current is lower than predicted, which would normally be ascribed to parasitic series resistance, but in this case the data cannot be fit by assuming series resistance at high bias. A similar effect has been seen in other reports on GaAsBi diodes [15,16]. This report will focus on the regime in which the diode behaviours can be well-fitted using the Shockley diode equation.…”
Section: Resultssupporting
confidence: 76%
“…Muhammetgulyyev et al have also presented a GaAsBi‐based bulk solar cell. [ 47 ] They found a comparable V OC to Richards et al and Hasegawa et al, at 0.47 V, which they attributed to the formation of a Schottky junction between the p‐GaAs and the GaAsBi i‐region, caused by the formation of metallic Bi clusters. Ultimately, it is probably necessary to strain‐balance a GaAsBi‐based solar cell, potentially with a similar design to the 2011 world record cell, [ 51 ] which contained an InGaAsN layer, for example, by using GaAsBiN.…”
Section: Recent Progress On Gaasbi Devicesmentioning
confidence: 54%
“…Several groups have reported experimental results from GaAsBi‐based cells. [ 45–48 ] Some focused on multiple quantum well (MQW) designs, which are advantageous because they can decouple the absorption edge and average lattice constant. [ 49 ] Richards et al reported a series of GaAsBi/GaAs MQW diodes containing between 3 and 63 QWs.…”
Section: Recent Progress On Gaasbi Devicesmentioning
confidence: 99%
“…Compared with the thermionic emission theory, the diffusion theory applies to low-mobility semiconductors, and its equation is very similar to the thermionic emission theory. However, a difference in the saturation current density is noted as follows: 88,93 where D e is the diffusion coefficient, N c is the density of states in the conduction band, and N d is the donor density. Compared with the saturation current density J ST of thermionic emission theory, J SD is more dependent on the voltage variation and less sensitive to the temperature.…”
Section: Basics and Device Geometries Of Photodetectorsmentioning
confidence: 99%